Vertical Mandibular Range of Motion in Anesthetized Dogs and Cats - Gracis, Margherita; Zini, Eric (Frontiers in Veterinary Science, 2016)
The main movement of the temporomandibular joint of dogs and cats is in vertical dimensions (opening and closing the mouth). An objective evaluation of the vertical mandibular range of motion (vmROM) may favor early diagnosis of a number of conditions affecting the joint mobility. vmROM, corresponding to the maximum interincisal opening, was measured in 260 dogs and 127 cats anesthetized between June 2011 and April 2015 because of oral or maxillofacial problems and procedures. Animals with a known history of or having current diseases considered to hamper mandibular extension were excluded from the study. Dogs were divided into 4 subgroups, based on body weight: subgroup 1 (≤ 5.0 kg, 51 dogs), subgroup 2 (5.1 to 10.0 kg, 56 dogs), subgroup 3 (10.1 to 25 kg, 66 dogs) and subgroup 4 (> 25.1 kg, 87 dogs). The mean vmROM of all dogs was 107 ± 30 mm (median 109, range 40-180); in subgroup 1 was 67 ± 15 mm (median 67, range 40-100), in subgroup 2 was 93 ± 15 mm (median 93, range 53-128), in subgroup 3 was 115 ± 19 mm (median 116, range 59-154) and in subgroup 4 was 134 ± 19 mm (median 135, range 93-180). The mean vmROM of the cats was 62 ± 8 mm (median 63, range 41-84). Correlations between vmROM, age, sex and body weight were evaluated. In dogs vmROM did not correlate with age and in cats a weak positive correlation was found. vmROM and body weight were positively correlated in both populations, except dog subgroup 2. Overall, mean vmROM and body weight were significantly higher in male than female, both in dogs and in cats. However, vmROM did not differ between sexes in any of the canine subgroups, and only in subgroup 4 male dogs were significantly heavier than females. Evaluation of vmROM should be incorporated into every diagnostic examination as it may be valuable in showing changes overtime for every single patient.